2013
DOI: 10.1063/1.4812484
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-magnetic stability of superconducting films controlled by nano-morphology

Abstract: , T. H. (2013). Thermo-magnetic stability of superconducting films controlled by nano-morphology. Applied Physics Letters, 102 (25), 252601-1-252601-5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…From this point of view, the origin of dendritic instabilities would remain unexplained. However, independent scanning electron microscopy (SEM) study in [8] showed that, seemingly in correlation with Tc and ρn, one of the films showed granular nanostructure, and another did not. It was the film with welldefined nano-grains that demonstrated dendritic instabilities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From this point of view, the origin of dendritic instabilities would remain unexplained. However, independent scanning electron microscopy (SEM) study in [8] showed that, seemingly in correlation with Tc and ρn, one of the films showed granular nanostructure, and another did not. It was the film with welldefined nano-grains that demonstrated dendritic instabilities.…”
Section: Resultsmentioning
confidence: 99%
“…This behaviour is unexpected. The film has parameters such as critical temperature or resistivity much better than in any NbN films deposited previously, and according to [8], it should not show dendritic instabilities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, nano-scaled defects, which enhance the critical current density and the Joule heating, have proven to favor the development of vortex instabilities in the form of quasi-one-dimensional micro-jumps in nano-granular samples of NbN due to the rise of the local electrical fields. 72 In addition to the experimental particularities and previous results mentioned above, and in order to shed light on any possible contribution from the MW electric and magnetic fields to the observed jump-like magnetic response, the values of the parallel and perpendicular components of E and H were estimated at the edge of the CS. The results obtained for constant values of referent nominal power (P = 0 dBm), frequency value ( f = 1.06 GHz), and Q factor (50) were found to be E ∥ ≃ 1000 V/m, E ⊥ ≃ 850 V/m, and H ∥ ≈ H ⊥ ≃ 0.1 Oe.…”
Section: B Swept-frequency Magnetic Measurementsmentioning
confidence: 99%